Faster autotrophic growth of anaerobic ammonium-oxidizing microorganisms in presence of nitrite, using inocula from colombia (2014)
Título en español: Crecimiento rápido autotrófico de microorganismos anaerobios oxidadores de amonio en presencia de nitrito, usando inóculos de ColombiaShort Title: Growth from Colombian inoculated anammoxSummary: Anammox is a nitrite dependent process, catalyzed by bacteria of the order Brocadiales. Anammox bacteria oxidize ammonia under anoxic conditions, with nitrite as electron acceptor producing dinitrogen gas. Here, we demonstrated the presence of anammox bacteria by enriched them in a SBR reactor, with anaerobic samples taken from de bottom of a pond used in primary wastewater treatment. The enrichment reached nitrogen (N) removal rates of nearly 1.92kg N/m3/day. (The stoichiometry of the reaction matched previous anammox studies). The enriched bacterial communities were analyzed by Fluorescence In situ Hybridization (FISH), and showed nearly a 90% of enrichment at the end of the experiment (day 90). As far as we know, this is the first time that the anammox bacteria were enriched using Colombian inocula. The enrichment was achieved in relatively short time with high yields and has an excellent potential for application in wastewater treatment opening the opportunity to treat nitrogen-rich effluents by partial nitritation and anammox, thereby decreasing operational costs with respect to aeration (nitrification) and addition of organic electron donor (heterotrophic denitrification). This more sustainable treatment is a good alternative to control nutrient pollution in water bodies in tropical countries.Key words: nitrogen cycle; advanced treatment; anammox;  nitritation; nitratation; denitrification.Resumen: La oxidación anaerobia del amonio (anammox), es un proceso nitrito dependiente, catalizado por bacterias del filo planctomicetes. Estas bacterias oxidan el amonio en ausencia de oxígeno, con nitrito como aceptor de electrones produciendo nitrógeno molecular. En Colombia, demostramos la presencia de estas bacterias mediante el enriquecimiento de cultivos en reactores por lotes, con inóculos nativos, provenientes de muestras anaeróbias tomadas del fondo de una laguna para el tratamiento primario de aguas residuales. El enriquecimiento logrado alcanzó remociones de nitrógeno (N), en el orden de 1.92kg - N /m3/día (la estequiometria de la reacción estuvo acorde con estudios previos de anammox). La comunidad bacteriana enriquecida, se analizó mediante hibridación en sitio con fluorescencia (FISH), y mostró que el enriquecimiento contenía aprox. 90 % de bacterias anammox al final del experimento (Día 90). Esta es la primera vez que en Colombia se logra el enriquecimiento de estas bacterias con inóculos locales, hasta nuestro conocimiento. El enriquecimiento fue alcanzado en relativamente corto tiempo con altos rendimientos y tiene un excelente potencial de aplicación en el tratamiento de aguas residuales, abriendo oportunidades para el tratamiento de efluentes ricos en nitrógeno mediante nitritación parcial y anammox, disminuyendo los costos en los procesos de aireación (nitrificación) y en la de adición de donadores orgánicos (denitrificación heterótrofa). El uso de estos tratamientos más sostenibles es una buena alternativa para el control de contaminación por nutrientes en los cuerpos de agua, en países tropicales.Palabras clave: Ciclo del Nitrógeno; Tratamiento avanzado;  anammox; nitritación; nitratación; denitrificación.